3D interslab echo‐shifted FLASH sequence for susceptibility weighted imaging. Issue 1 (24th August 2015) - Ma, Ya‐Jun; Liu, Wentao; Zhao, Xuna; Tang, Weinan; Li, Huanjie; Fan, Yang; Tang, Xin; Zhang, Yaoyu; Gao, Jia‐Hong
Abstract : Purpose: To develop a novel three‐dimensional (3D) sequence for susceptibility weighted imaging that is able to reduce scan time substantially while maintaining high image signal‐to‐noise ratio (SNR). Methods: The proposed fast T2 *‐weighted sequence was based on a 3D full‐balanced gradient frame and a pair of crusher gradients. The pair of crusher gradients were used to shift MR signal from the repetition time where the MR signal was originated to a later repetition time to enhance T2 * weighting. To avoid image SNR reduction due to the repeated signal excitations by later RF pulses, as it would occur for typical echo‐shifted (ES) FLASH, an interslab scan mode for the fast T2 *‐weighted sequence was introduced for signal acquisition. The effectiveness of this novel sequence was evaluated by comparing it with 3D FLASH and ES‐FLASH sequences. Results: The proposed interslab ES T2 *‐weighted sequence was able to reduce the scan time by half with a SNR comparable to the typical multislab FLASH. Besides, it yielded a higher image SNR than the traditional multislab ES‐FLASH and was more flexible than the whole‐volume ES‐FLASH. Conclusion: An interslab ES sequence was developed with high time efficiency and relatively high image SNR compared with the conventional acquisition sequences. Magn Reson Med 76:222–228, 2016. © 2015 Wiley Periodicals, Inc.